2012
DOI: 10.5152/jtgga.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of metabolic syndrome in women with polycystic ovary syndrome

Abstract: Objective: To identify biochemical factors that serve as predictors for the metabolic syndrome (MetS) in patients with polycystic ovary syndrome (PCOS) and to investigate the value of adipocytokines in the prediction of metabolic syndrome. Material and Methods:A total of 91 pre-menopausal women with PCOS diagnosed according to the Rotterdam consensus criteria were recruited as study subjects. Waist circumference, blood pressure, body mass index (BMI), fasting glucose, serum lipids, insulin, FSH, LH, E 2 , tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In numerous published studies, authors identified various markers for predicting PCOS risk, including coagulation parameters, sex-hormone binding globulin, irisin, betatrophin, zinc-alpha-glycoprotein, and leptin. 27,28 To the best of our knowledge, our study is the first to evaluate the relationship between alarin and PCOS status in women with infertility. Our study differs from other studies by evaluating infertile controls and PCOS group with infertility.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous published studies, authors identified various markers for predicting PCOS risk, including coagulation parameters, sex-hormone binding globulin, irisin, betatrophin, zinc-alpha-glycoprotein, and leptin. 27,28 To the best of our knowledge, our study is the first to evaluate the relationship between alarin and PCOS status in women with infertility. Our study differs from other studies by evaluating infertile controls and PCOS group with infertility.…”
Section: Discussionmentioning
confidence: 99%
“…They found ghrelin levels to be lower in women with PCOS and also lower still in patients with hyperandrogenaemia. Ersan et al (29) investigated the relationship between adipocytokines and metabolic syndrome in pre-menopausal women with PCOS; adiponectin was found to be significantly lower and leptin was significantly higher in patients with PCOS and metabolic syndrome. However, in a recent study, the levels of metabolic risk markers like adiponectin, leptin and ghrelin were measured in obese adolescents with and without PCOS; all were found to be similar in both groups (30).…”
Section: Metabolic Markers Of Metabolic Syndrome In Pcosmentioning
confidence: 99%
“…[2] In various studies, this increased cardiometabolic risk has been mainly attributed to increased visceral fat as visceral fat is the main source of free fatty acids and inflammatory cytokines. [23456] About 50–60% of women with PCOS have central body fat distribution. [3] Thus, in women with PCOS assessing visceral adipose dysfunction at a younger age should help in preventing the future cardiometabolic complications by either lifestyle modification or medical treatment.…”
Section: Introductionmentioning
confidence: 99%